2020
DOI: 10.21203/rs.3.rs-40911/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrafast molecular orbital tomography of a pentacene thin film using time-resolved momentum microscopy at a free-electron laser

Abstract: Understanding and control of photon-induced dynamics of molecules on solid surfaces, including atomic rearrangements as well as charge transfer and non-equilibrium electron dynamics, are of essential importance for surface chemistry but also for the development of new devices. We use time-resolved momentum microscopy at a free-electron laser (FEL) and extend orbital tomography to time-resolved imaging of electronic wave functions of excited molecular orbitals. This technique will provide unprecedented insight … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The system thus specifically enables k z -selective probing of ultrafast electronic structure dynamics in 3D materials as well as ultrafast 3D orbital tomography of molecular layers. 32,63 Moreover, the setup complements time-resolved momentum microscopy in the XUV to soft x-ray regime at the FEL FLASH, for which the same ToF momentum microscope is used. 21 The two complementary probe photon sources particularly enable a unique merging of trARPES with time-resolved x-ray photoelectron spectroscopy [64][65][66] and diffraction 67 for combined investigations of ultrafast electronic, chemical, and geometric structure dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The system thus specifically enables k z -selective probing of ultrafast electronic structure dynamics in 3D materials as well as ultrafast 3D orbital tomography of molecular layers. 32,63 Moreover, the setup complements time-resolved momentum microscopy in the XUV to soft x-ray regime at the FEL FLASH, for which the same ToF momentum microscope is used. 21 The two complementary probe photon sources particularly enable a unique merging of trARPES with time-resolved x-ray photoelectron spectroscopy [64][65][66] and diffraction 67 for combined investigations of ultrafast electronic, chemical, and geometric structure dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The ToF set-up has shown great promise in the VUV and soft X-ray regimes. [198][199][200] Medjanik et al demonstrated the first instance of applying this novel ToF kmicroscope to fully map the bulk electronic structure of tungsten in the soft X-ray regime. [141] In comparison to conventional ARPES with a dispersive analyser, this approach greatly simplified the process route to map the 4D spectral density function.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[129,136,288] Proof-of-principle experiments have been performed for a number of exciting emerging applications of time-resolved momentum microscopy, including ultrafast molecular orbital imaging and tracking transient changes of topological properties and orbital texture of out-of-equilibrium states of matter, where currently XUV excitation energies are used, but which could be translated into the hard X-ray regime in the future. [199,[390][391][392] A new powerful tool, that is already using hard X-rays, is emerging in the form of full-field photoelectron diffraction for structural analysis, which has been demonstrated in first static experiments using hard X-rays. [204,205] A serious obstacle for time resolved studies is the Coulomb interaction of electrons confined in a small spatio-temporal phase-space volume.…”
Section: Outlook and Futurementioning
confidence: 99%